Quantitative flow ratio-based outcomes in patients undergoing transcatheter aortic valve implantation quaestio study - Demola, Pierluigi; Colaiori, Iginio; Bosi, Davide; Musto D’Amore, Sergio; Vitolo, Marco; Benatti, Giorgio; Vignali, Luigi; Tadonio, Iacopo; Gabbieri, Davide; Losi, Luciano; Magnavacchi, Paolo; Sgura, Fabio Alfredo; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary artery disease (CAD) is common in patients with aortic valve stenosis (AS) ranging from 60% to 80%. The clinical and prognostic role of coronary artery lesions in patients undergoing Transcatheter Aortic Valve Implantation (TAVI) remains unclear. The aim of the present observational study was to estimate long-term clinical outcomes by Quantitative Flow Ratio (QFR) characterization of CAD in a well-represented cohort of patients affected by severe AS treated by TAVI. Methods A total of 439 invasive coronary angiographies of patients deemed eligible for TAVI by local Heart Teams with symptomatic severe AS were retrospectively screened for QFR analysis. The primary endpoint of the study was all-cause mortality. The secondary endpoint was a composite of cardiovascular mortality, stroke/transient ischemic attack (TIA), acute myocardial infarction (AMI), and any hospitalization after TAVI. Results After exclusion of patients with no follow-up data, coronary angiography not feasible for QFR analysis and previous surgical myocardial revascularization (CABG) 48/239 (20.1%) patients had a QFR value lower or equal to 0.80 (QFR + value), while the remaining 191/239 (79.9%) did not present any vessel with a QFR positive value. In the adjusted Cox regression analysis, patients with positive QFR were independently associated with an increased risk of all-casual mortality (Model 1, HR 3.47, 95% CI, 2.35−5.12; Model 2, HR 5.01, 95% CI, 3.17−7.90). In the adjusted covariate analysis, QFR+ involving LAD (37/48, 77,1%) was associated with the higher risk of the composite outcome compared to patients without any positive value of QFR or non-LAD QFR positive value (11/48, 22.9%). Conclusions Pre-TAVI QFR analysis can be used for a safe, simple, wireless functional assessment of CAD. QFR permits to identify patients at high risk of cardiovascular mortality or MACE, and it could be considered by local Heart Teams.